2015
DOI: 10.1093/toxsci/kfv017
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel Facilitates Endothelial Dysfunction through Oxidative Stress via Modulation of Protein Kinase C Beta: The Protective Effects of Sotrastaurin

Abstract: Docetaxel (DTX), a taxane drug, has widely been used as an anticancer or antiangiogenesis drug. However, DTX caused side effects, such as vessel damage and phlebitis, which may reduce its clinical therapeutic efficacy. The molecular mechanisms of DTX that cause endothelial dysfunction remain unclear. The aim of this study as to validate the probable mechanisms of DTX-induced endothelial dysfunction in endothelial cells. Human umbilical vein endothelial cells (HUVECs) were stimulated with DTX (2.5, 5, and 10nM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
4
24
1
Order By: Relevance
“…One molecular mechanism of DTX causing endothelial dysfunction is DTX-induced ROS formation. [29][30][31][32][33] Here, low CDO1 methylation may be a useful marker to stratify patients for DTX treatment comparable to anthracycline treatment in breast cancer patients. 7 However, this is highly speculative and further studies are needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One molecular mechanism of DTX causing endothelial dysfunction is DTX-induced ROS formation. [29][30][31][32][33] Here, low CDO1 methylation may be a useful marker to stratify patients for DTX treatment comparable to anthracycline treatment in breast cancer patients. 7 However, this is highly speculative and further studies are needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first case of scleroderma secondary to docetaxel with organ involvement (PAH and renal scleroderma crisis) has been published (131). One of the explanations would be the possibility of endothelial cell damage induced by oxidative stress secondary to docetaxel (132).…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…It has been hypothesized that PAH in systemic sclerosis occurs as a consequence of progressive remodeling of pulmonary vasculature with inflammation and endothelial injury as common precursors. A recent study revealed that docetaxel facilitates endothelial injury through oxidative stress mechanism [ 12 ]. Thus, docetaxel may induce PAH either by oxidative injury to the endothelial cells or by stimulating fibroblast cells as mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%